Autophagy and Autoimmunity Crosstalks - Bhattacharya, Abhisek; Eissa, N. Tony (Frontiers in Immunology, 2013)
Autophagy, initially viewed as a conserved bulk-degradation mechanism, has emerged as a central player in a multitude of immune functions. Autophagy is important in host defense against intracellular and extracellular pathogens, metabolic syndromes, immune cell homeostasis, antigen processing and presentation and maintenance of tolerance. The observation that the above processes are implicated in triggering or exacerbating autoimmunity raises the possibility that the autophagy pathway is involved in mediating autoimmune processes, either directly or as a consequence of innate or adaptive functions mediated by the pathway. Genome-wide association studies have shown association between single nucleotide polymorphisms (SNPs) in autophagy related gene 5 (Atg5), and Atg16l1 with susceptibility to systemic lupus erythematous (SLE) and Crohn’s disease, respectively. Enhanced expression of Atg5 was also reported in blood of mice with experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis (MS), and in T cells isolated from blood or brain tissues from patients with active relapse of MS. This review explores the roles of autophagy pathway in the innate and adaptive immune systems on regulating or mediating the onset, progression or exacerbation of autoimmune processes.